THE EFFECT OF DIGITAL TECHNOLOGY ON THE OUTCOME OF LEARNING TO COOK INDEPENDENTLY IN THE CULINARY COMMUNITY - Winanti . .; Ahadi . . (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2022)
ABSTRACTThe Effect of Digital Technology on Learning Outcomes of Independent Cooking in the Culinary Community the Covid-19 pandemic has changed people''s culture in consuming food. Many activities are done at home and cooking is an alternative to pass the time. For some people, cooking is a business opportunity to increase their income. For people who rarely and never even cook, this is the right moment to start learning to cook. the existence of social media, technology platforms, smartphones, and the internet make it easier for people to learn to cook independently both at home and in various places. The purpose of this study was to determine the effect of digital technology on the results of learning to cook independently in the Culinary Community. From the results of the questionnaire that was filled out by 72 respondents, it was found that technology has an influence of 64.5% on the results of learning to cook independently, and 35% is influenced by other variables. This shows that the existence of digital technology cannot be separated in human life today, especially in the digital era which is all technology-based.Keywords: Digital technology, Learning, Cook independently, Culinary, Community